Combustion and Emission Characteristics of Diesel Engines Fuelled with Waste Plastic Oil Blends and Emulsions - Mithai Khalandhar Basha; Dr.D.R.Srinivasan; D. Raja Kulayappa; Dr. Arekanti Nagaraju (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Diesel engines convert chemical energy into thermal energy and subsequently into mechanical energy using mechanical components. They play a vital role in power generation, agriculture, and mass transportation sectors. Due to increasing energy demands, stringent emission regulations, and depletion of fossil fuel resources, there is a pressing need to identify alternative fuels for internal combustion engines. Plastic materials, known for their lightweight, corrosion resistance, low cost, and reusability, have become integral to modern life and industrial applications. However, the disposal of waste plastics poses serious environmental challenges due to their large volumes and the complexity of degradation. Plastics, primarily composed of hydrocarbons derived from petroleum, also contain additives like antioxidants, colorants, and stabilizers. Pyrolysis, a chemical feedstock recycling technique, converts waste plastics into oil that can be used as an alternative fuel in diesel engines without modifications. However, using Waste Plastic Oil (WPO) alone tends to increase harmful emissions like Carbon Monoxide (CO), Oxides of Nitrogen (NOx), and Unburnt Hydrocarbons (UBHC) compared to conventional diesel. This study investigates the combustion, performance, and emission characteristics of a single-cylinder, air-cooled, direct injection (DI) diesel engine using three types of WPO-based fuel blends at various engine loads with a constant speed of 1500 rpm. a) WPO-diesel blends (10% and 20% diesel by volume), b) WPO-Jatropha Methyl Ester (JME) blends, c) WPO-water emulsion blends (10%, 20%, 30% water by volume)